Desenvolvimento de ligas multicomponentes à base de Fe-Cr para aplicação na indústria de papel e celulose - Bertolo, Virgínia Morete Barbosa (2018)
The constant exposure to extremely corrosive environments in the pulp and paper industry normally generate onerous costs, requiring the optimization of the materials currently used in the application. The multicomponent alloys, through their differentiated configuration, have excellent properties, interesting sectors of several industrial sectors that require materials with excellent performance under harsh environments. This work aims to develop multi-component Fe-Cr-based alloys of unprecedent composition for application in the pulp and paper industry through thermodynamic simulations using the CALPHAD method, the microstructural characterization of the alloys by XRD and SEM, and corrosion resistance analysis by conducting polarization tests. The developed alloys refer to two biphasic alloys, composed of laves phase and solid solutions bcc and hcp, and one exclusively of bcc. The melting process of the alloys that contain Laves phase in their microstructure was of considerably complex due to the constant ingot fracture. The alloy’s microstructural composition was varied, not only the typical dendritic phase being present, but also independent grains and eutectic phases. Specifically, the Fe15Cr15Nb18Ni27Al25 alloy presented microstructural heterogeneities caused by the lack of composition homogenization. It was also difficult to melt the alloy with Mn in its composition due to the constant projection of the element during the process. Comparing the XRD results with the thermodynamic simulations, these were efficient. In terms of corrosion resistance, Fe15Cr15Nb18Ni27Al25 and Fe16Cr16Nb16Zr25Sn27 alloys, both of biphasic microstructure, were considered promising for application in the pulp and paper industry.